Review of Levetiracetam as a First Line Treatment in Status Epilepticus in the Adult Patients – What Do We Know so Far? - Davis, Robin; Shin, Hae Won (Frontiers in Neurology, 2013)
With the advent of new antiepileptic drugs comes the potential for significant advances in the emergent management of status epilepticus. Traditional antiepileptic drugs possess side effect profiles that may limit their clinical utility or lead to increased patient morbidity or mortality. The relatively recent development of levetiracetam shows promise for effective control of acute status epilepticus in adults, but current objective data of its use as a first-line agent for control of status is quite limited. This paper serves to examine existing literature while considering levetiracetam as a first-line therapy in status in the adult patient population. Indeed, existing studies are narrow in their scope, however the present data do lay a substantial foundation for further investigation of levetiracetam as a primary therapy in acute status epilepticus.